Sentence Structure of Interrogative Sentences in “After You” Novel - Ni Wayan Yuni Damayanti; I Gusti Bagus Wahyu Nugraha Putra; Putu Devi Maharani (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
This study aims to analyse the types of interrogative sentences in “After You” Novel and draw the tree diagram. Qualitative method is used to identify the problem and descriptive method also used to explain the analysis. The data took from interrogative sentences in After You Novel. Based on Quirk et al (1985) theory there are 565 interrogative sentences found. The finding is divided into two types there are 227 sentences are belonged to Wh-question and 338 sentences are categorized as Yes-no question. Wh-question divided into two categories 222 sentences categorized as positive Wh-question and 5 sentences belonged to negative Wh-question. Yes-no question divided into five there are 157 sentences categorized as positive yes-no question, 92 sentences categorized as declarative yes-no question, 48 sentences categorized as yes-no question with modal auxiliary, 30 sentences as tag question and 11 sentences as negative yes-no question. Brown and Miller (1991) as guidance theory to draw the tree diagram which need to attach the wh-question word or the auxiliary to the Complementizer.